Relationship Between the Green and Lyapunov Functions in Linear Extensions of Dynamical Systems - Hrod, I. M.; Kulik, V. L. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We study systems of linear extensions for dynamical systems. As a result, we establish the relationship between the design matrices in the structure of Green functions and alternating Lyapunov functions.